APLIKASI KARTU KATA (FLASH CARD) UNTUK KETERAMPILAN MENULIS BAHASA JERMAN PESERTA DIDIK KELAS X SEMESTER 1 - Yuniar, Indah; Wahyuningsih, Fahmi (LATERNE, 2022)
Learning media is a tool in learning that can be used by teachers in conveying information to stimulate students to acquire knowledge during learning activities. Word cards (flash card) is tangible media cards with sizes that can be changed as needed and consist of: pictures, words or simple sentences that can facilitate learning activities to be more fun and effective. Learning during the COVID-19 pandemic is happening offline and online, so it is necessary to develop media such as word card applications (flash card) that can be used during online and offline learning activities. The formulation of the problem from this article is how the process of developing a word card applications (flash card) for German writing skills. This research aims to develop a word card applications (flash card) and determine the feasibility of Learning media based on validation from experts. The research method of this article applies the 4D development model (Four-D model) developed by Thiagarajan. The data source of this article is andere Vorstellen material from the book Deutsch ist Einfach 1, internet and validator. The assessment instrument of this article is the learning media validation questionnaire sheet. The results of the validation of this Learning media obtained a percentage of 86.1% with very good eligibility criteria.